Shortcomings of the dissipation rate for understanding the turbulent environment of plankton—And a potential solution - Peter J. S. Franks; Bryce G. Inman (Limnology and Oceanography, 2024)
Fundamental marine ecosystem dynamics such as mating, predation, and infection require individual plankton to move relative to one another. Ambient turbulence is often invoked as a mechanism to facilitate such interactions. The local intensity of turbulence is quantified as the dissipation rate of turbulent kinetic energy. While the dissipation rate is central to understanding large‐scale fluxes of heat, salt, and nutrients in the ocean, we show that it can be a poor descriptor of the turbulent environment experienced by individual plankton. A dissipation rate is a single integrated quantity representing all the complex motions in a turbulent region; the instantaneous turbulent environment of plankton may bear little resemblance to that predicted by the dissipation rate or quantities derived from it. Most importantly, the statistics (probabilities) of the relative motions of plankton in turbulence cannot be recovered from the dissipation rate or its spectrum: the probabilities of the plankton experiencing any given turbulent relative velocity are lost in the calculation. This presents a fundamental barrier to our understanding of the effects of ambient turbulence on planktonic ecosystem dynamics in the ocean. Rather than relying on dissipation rates, we show that quantifying the probability distributions of the microscale turbulent motions can provide much richer insights into the turbulent environment of individual plankton. Expanding such statistical analyses, and improving our understanding of the Lagrangian properties of ocean turbulence as experienced by plankton in the ocean will lead to significant increases in our ability to understand and quantify the effects of turbulence on plankton.

Oceanic turbulence from a planktonic perspective - Peter J. S. Franks; Bryce G. Inman; Jennifer A. MacKinnon; Matthew H. Alford; Amy F. Waterhouse (Limnology and Oceanography, 2022)
The potential influences of turbulence on planktonic processes such as nutrient uptake, grazing, predation, infection, and mating have been explored in hundreds of laboratory and theoretical studies. However, the turbulence levels used may not represent those experienced by oceanic plankton, bringing into question their relevance for understanding planktonic dynamics in the ocean. Here, we take a data‐centric approach to understand the turbulence climate experienced by plankton in the ocean, analyzing over one million turbulence measurements acquired in the open ocean. Median dissipation rates in the upper 100 m were −8 W kg −1 , with 99% of the observations −6 W kg −1 . Below mixed layers, the median dissipation rate was ~ 10 −10 W kg −1 , with 99% of the observations −7 W kg −1 . Even in strongly mixing layers the median dissipation rates rarely reached 10 −5 W kg −1 , decreasing by orders of magnitude over 10 m or less in depth. Furthermore, episodes of intense turbulence were transient, transitioning to background levels within 10 min or less. We define three turbulence conditions in the ocean: weak ( −8 W kg −1 ), moderate (10 −8 –10 −6 W kg −1 ), and strong (> 10 −6 W kg −1 ). Even the strongest of these is much weaker than those used in most laboratory experiments. The most frequent turbulence levels found in this study are weak enough for most plankton—including small protists—to outswim them, and to allow chemical plumes and trails to persist for tens of minutes. Our analyses underscore the primary importance of planktonic behavior in driving individual interactions.